A gate at the stairs [large type] : a novel - Moore, Lorrie (Thorndike Press large print core, 2010)
As the United States begins gearing up for war in the Middle East, twenty-year-old Tassie Keltjin, the Midwestern daughter of a gentleman hill farmer--his 'Keltjin potatoes' are justifiably famous--has come to a university town as a college student, her brain on fire with Chaucer, Sylvia Plath, Simone de Beauvoir. Between semesters, she takes a job as a part-time nanny. The family she works for seems both mysterious and glamorous to her, and although Tassie had once found children boring, she comes to care for, and to protect, their newly adopted little girl as her own. As the year unfolds and she is drawn deeper into each of these lives, her own life back home becomes ever more alien to her: her parents are frailer; her brother, aimless and lost in high school, contemplates joining the military. Tassie finds herself becoming more and more the stranger she felt herself to be, and as life and love unravel dramatically, even shockingly, she is forever changed.